Say if you had the pattern 15 20 25 30 35 40 45 50 To find the nth term you have to see what the gap between the numbers is. In our case this is 5. Then you have to find out what the difference between the gap and the first number. In this sequence it is 10. So your answer would be..... 5n+10 That's how you find the nth term.
The nth term in this sequence is 4n + 3.
The next term is: 15+4 = 19 The nth term is: 4n-5
If you mean: 15 11 7 3 then the nth term is 19-4n
It is: nth term = 5-4n and so the next term will be -19
It is: nth term = 29-7n
The nth term is: 5n
1...2....3....43...7...11..157 - 3 = 411 - 7 = 415 - 11 = 4(the start of the nth term is 4n)4 x 1 = 4(but the first term is 3, so...)4 -1 = 3nth term = 4n - 1
The nth term is 4n-1 and so the next term will be 19
The nth term is 18 -3n and so the next term will be 3
If you mean -1 3 7 11 15 then the nth term is 4n-5 and so the next term will be 19
1, 3, 6, 10, 15 ,21 The nth term for the sequence (where you replace n with the term you want to find) is: (n(n+1))/2
The nth term is -7n+29 and so the next term will be -6
This is an arithmetic progression. In general, If an A.P. has a first term 'a', and a common difference 'd' then the nth term is a + (n - 1)d. In the sequence shown in the question, the first term is 0 and the common difference is 5, therefore the nth term is, 0 + (n - 1)5. This can be rearranged to read : 5(n - 1) For example : the 7th term is 30 : 5(7 - 1) = 5 x 6 = 30.
The nth term is: 2n+7 and so the next number will be 19
The nth term for that arithmetic progression is 4n-1. Therefore the next term (the fifth) in the sequence would be (4x5)-1 = 19.
It is: 2n+9
8n + 7
7n - 6
In order to find the nth term, you need to see the difference between the numbers first, so you can see that here, the numbers keep getting smaller by 6. Therefore, the equation must be the term = something (x) -6n. To find that x, you have to look at any of the numbers, for example, 15. You know that n=1 in this case because it is the first number so 15 = x - (6*1) 15 = x - 6 (now add 6 to both sides) 21 = x So you now know that the nth term = 21 - 6n